Pengaruh Lingkungan Keluarga dan Lingkungan Sosial terhadap Manajemen Keuangan Generasi Sandwich - Handayani, Andi Asti; Supatminingsih, Tuti (ARZUSIN, 2026)
The increasing phenomenon of the sandwich generation has become an important issue because this group faces financial responsibilities toward two generations simultaneously, thereby requiring good financial management skills. This study aims to analyze the influence of family environment and social environment on the financial management of the sandwich generation in Makassar City. This study used a quantitative approach with an explanatory survey design. Data were collected through the distribution of questionnaires to 150 respondents selected using a purposive sampling technique. Data analysis was conducted using the JASP application through validity testing, reliability testing, descriptive analysis, and multiple linear regression. The results show that family environment and social environment have a positive and significant influence on the financial management of the sandwich generation. Family environment is the most dominant variable, with a β coefficient value of 0.633, whereas social environment has a β value of 0.445. The coefficient of determination (R²) of 0.577 indicates that 57.7% of the variation in financial management can be explained by family environment and social environment. The conclusion of the study affirms that family environment and social environment play an important role in shaping the financial management behavior of the sandwich generation. The implications of this study provide theoretical contributions to the development of financial behavior studies, as well as practical implications for families, government, and financial institutions in improving financial literacy and financial management among the productive-age population.